PERAN GURU PENGGERAK DALAM MEWUJUDKANMERDEKA BELAJAR DAN TRANSFORMASI PENDIDIKAN - Sri Yomila Putri; Ismira Dewita (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2024)
This research aims to analyze the role of driving teachers in realizing Freedom of Learning and educational transformation in Indonesia. This research uses a qualitative approach with literature methods. The research results show that driving teachers play a crucial role in realizing the vision of Merdeka Belajar through innovative teaching practices, responsive and relevant curriculum development, and the creation of a learning environment that is conducive for students to develop. Driving teachers become agents of change who encourage students to become more independent, creative and critical. They also facilitate project-based learning, collaborative learning, and the effective use of educational technology.